2010
DOI: 10.1007/s10509-010-0533-5
|View full text |Cite
|
Sign up to set email alerts
|

Ion acoustic solitons of KdV and modified KdV equations in weakly relativistic plasma containing nonthermal electron, positron and warm ion

Abstract: In this paper, the ion-acoustic solitons in a weakly relativistic electron-positron-ion plasma have been investigated. Relativistic ions, Maxwell-Boltzmann distributed positrons and nonthermal electrons are considered in collisionless warm plasma. Using a reductive perturbation theory, a Korteweg-de Vries (KdV) equation is derived, and the relativistic effect on the solitons is studied. It is found that the amplitude of solitary waves of the KdV equation diverges at the critical values of plasma parameters. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…Plasmas 19, 012113 (2012) the Maxwell' (dotted line) distribution (parametric values of j are taken from the Refs. [41][42][43]. It can also be verified the relation stated above i.e., j ¼ 1=1 À q between kappadistribution and q-distribution from those figures.…”
Section: -2supporting
confidence: 82%
See 1 more Smart Citation
“…Plasmas 19, 012113 (2012) the Maxwell' (dotted line) distribution (parametric values of j are taken from the Refs. [41][42][43]. It can also be verified the relation stated above i.e., j ¼ 1=1 À q between kappadistribution and q-distribution from those figures.…”
Section: -2supporting
confidence: 82%
“…Leubner 38 suggested a nonextensive approach to provide some fundamental reasoning for the occurrence of j-distributions, a reduced j-distribution, which can be transformed into q-nonextensive distribution by the expression j ¼ 1=1 À q (Refs. [39][40][41][42][43], is obtained. The standard j distribution is known now close to the qnonextensive distribution, however, there is no simple transformation between the two distributions as their arguments and powers do not fit the same transformation.…”
Section: Introductionmentioning
confidence: 99%
“…We apply the reductive perturbation theory (Nejoh [2]), to show that the amplitude of the perturbed ion density in a weakly relativistic warm plasma and superthermally distributed electrons in the smallwavenumber limit is governed by the K-dV equation. To show that we introduce the stretched variables and as (Pakzad and Gill et al [22][23])…”
Section: Derivation K-dv Equation For the Systemmentioning
confidence: 99%
“…In 2009, Malik et al studied the different mode in magnetoplasma by using the reductive perturbation method and concluded that phase velocity of the propagation mode depends on plasma density and ion temperature . In 2010, Pakzad studied the relativistic effects on solitons and showed that increase in the relativistic factor will affect the amplitude of compressive and rarefactive solitons differently . In 2012, Roy et al studied the solitary waves and double layers in an ultra‐relativistic degenerate dusty electron‐positron‐ion plasma and showed how the number densities of the particles in that plasma affect the solitary waves and double layer behaviour …”
Section: Introductionmentioning
confidence: 99%